Mechanoinduction of PTHrP/cAMP-signaling governs proteoglycan production in mesenchymal stromal cell-derived neocartilage - Lückgen, Janine; Diederichs, Solvig; Raqué, Elisabeth; Renkawitz, Tobias; Richter, Wiltrud; Buchert, Justyna (Journal of cellular physiology, 2024)
Abnormal mechanical loading is one of the major risk factors for articular cartilage degeneration. Engineered mesenchymal stromal cell (MSC)-derived cartilage holds great promise for cell-based cartilage repair. However, physiological loading protocols were shown to reduce matrix synthesis of MSC-derived neocartilage in vitro and the regulators of this undesired mechanoresponse remain poorly understood. Parathyroid hormone-related protein (PTHrP) is involved in cartilage development and can affect extracellular matrix (ECM) production during MSC chondrogenesis opposingly, depending on a continuous or transient exposure. PTHrP is induced by various mechanical cues in multiple tissues and species; but whether PTHrP is regulated in response to loading of human engineered neocartilage and may affect matrix synthesis in a positive or negative manner is unknown. The aim of this study was to investigate whether dynamic loading adjusts PTHrP-signaling in human MSC-derived neocartilage and whether it regulates matrix synthesis and other factors involved in the MSC mechanoresponse. Interestingly, MSC-derived chondrocytes significantly upregulated PTHrP mRNA (PTHLH) expression along with its second messenger cAMP in response to loading in our custom-built bioreactor. Exogenous PTHrP(1-34) induced the expression of known mechanoresponse genes (FOS, FOSB, BMP6) and significantly decreased glycosaminoglycan (GAG) and collagen synthesis similar to loading. The adenylate-cyclase inhibitor MDL-12,330A rescued the load-mediated decrease in GAG synthesis, indicating a direct involvement of cAMP-signaling in the reduction of ECM production. According to COL2A1-corrected hypertrophy-associated marker expression, load and PTHrP treatment shared the ability to reduce expression of MEF2C and PTH1R. In conclusion, the data demonstrate a significant mechanoinduction of PTHLH and a negative contribution of the PTHrP-cAMP signaling axis to GAG synthesis in MSC-derived chondrocytes after loading. To improve ECM synthesis and the mechanocompetence of load-exposed neocartilage, inhibition of PTHrP activity should be considered for MSC-based cartilage regeneration strategies.
Veröffentlicht: 05 September 2024
Gesehen am 05.02.2025